FREQUENCY OF FACTORS LEADING TO THE DEVELOPMENT OF CLEFT LIP AND PALATE AT TERTIARY CARE HOSPITAL KARACHI - REHMAN , MU; KAKAR , A; REHM , AU; REHMAN , MU; ULLAH , N; KHAN , M; KAKAR , SU (Biological and Clinical Sciences Research Journal, 2024)
Cleft lip and palate are common congenital anomalies influenced by genetic and environmental factors. In Pakistan, these conditions pose significant challenges due to socio-economic and healthcare disparities. Objective: This study aimed to assess the frequency of factors contributing to cleft lip and palate among patients at a tertiary care hospital in Karachi. Methods: A cross-sectional study was conducted at the Plastic Surgery Department of Patel Hospital, Karachi, with a sample size of 127 patients determined using the WHO Sample Size Calculator. Data were collected using a structured questionnaire, including demographic information, maternal health behaviors, and clinical characteristics. Statistical analysis was performed using SPSS, with p-values <0.05 considered significant. Results: Maternal smoking during pregnancy was reported in 30% of cases, while inadequate folic acid intake was identified in 45% of participants. Consanguinity was observed in 50% of the sample. These factors were significantly associated with the occurrence of cleft anomalies. The findings align with global studies emphasizing the role of maternal smoking, nutritional deficiencies, and genetic predisposition in cleft etiology. Conclusion: This study identifies modifiable and non-modifiable risk factors contributing to cleft lip and palate in Pakistan. Public health interventions targeting maternal smoking cessation, folic acid supplementation, and awareness about the genetic risks of consanguinity are crucial for prevention. Future research should investigate genetic-environmental interactions to develop tailored strategies for at-risk populations.